Relationship between Waste Management and the Level of Fly Density at Kadompe Restaurants in Luwuk City - Maria Kanan; Dwi Wahyu Balebu; Bambang Dwicahya; Reflin Mamitoho (Poltekkes Kemenkes Palu, 2023)
The existence of waste can have an impact on public health because it becomes a means and source of transmission of various disease agents. The indirect effect of waste on health can be due to vector-borne disease agents that multiply in the waste. Buried waste can be used by flies as a breeding ground. This study aims to analyze the relationship between waste management and the level of fly density at Kadompe Restaurants in Luwuk City. This was an analytic survey with a cross-sectional design, namely by analyzing the relationship between waste management and the level of fly density at Kadompe Restaurants. The study population was all Kadompe Restaurants located on Maahas Coast in Luwuk City, Central Sulawesi Province as many as 33 restaurants. The study samples involved 26 restaurants which were selected using purposive sampling based on certain consideration, namely restaurants that were still active. The instrument for measuring Fly Density was a fly grill by referring to the Regulation of the Minister of Health of the Republic of Indonesia No. 50 of 2017. Data on waste management included sorting, container, transportation that were collected by direct observation at the Food Stall based on the observation sheet provided in accordance with Law no. 18 of 2008 concerning Waste Management. Data were analyzed using chi-square test with α ≤ 0.05. The results of the study statistically showed the values regarding waste sorting (p=0.382; RP= 1.071; 95% CI=0.936-1.227), waste container (p=0.713; RP=1.045; 95% CI=0.958-1.141), and waste transportation (p=0.234; RP=0.909; 95% CI=0.754-1.096). Based on the results of the study, it can be concluded that there was no relationship between waste sorting, container and transportation with the level of fly density at Kadompe Restaurants in Luwuk City. The Agency for the Environment (DLH) should be able to transport waste every day from Kadompe Restaurants located on Maahas coast in Luwuk City.